Etika Evaluasi Pembelajaran Pendidikan Agama Islam: Tinjauan Normatif dan Implementatif - Slamet Eko Syahroni; Kafilaturrahmah Kafilaturrahmah (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2026)
This study examines the ethics of evaluation in Islamic Religious Education (PAI) through a library research approach by integrating normative Islamic principles with implementative realities. The research objectives are to identify evaluation ethics principles based on the Qur’an and Hadith, analyze potentially unfair and discriminatory evaluation practices, formulate a comprehensive code of ethics for PAI evaluation, and develop an instrument for assessing PAI teachers’ professionalism. The findings indicate that evaluation ethics principles in Islam include justice (al-’adl), honesty (ash-shidq), objectivity (al-maudhu’iyyah), and responsibility (al-mas’uliyyah) grounded in tawhid values. Problematic evaluation practices include assessment bias, discrimination, result manipulation, and lack of transparency. The formulated code of ethics encompasses principles of honesty in measurement, objectivity in assessment, justice in scoring, and commitment to student development. The PAI teacher professionalism assessment instrument includes pedagogical, personality, social, and professional competency dimensions integrated with Islamic moral values.